CRITICAL THINKING SKILLS ON ARGUMENTATIVE TEXT WRITING SKILLS: DOES IT HAVE ANY EFFECT? - Audi Yundayani (UIN Alauddin Makassar, 2021)
Critical thinking is now often regarded as a necessary component of writing abilities. If this is confirmed, it is crucial to highlight students' ability to think critically to develop their writing skills. The purpose of this study is to investigate if students' critical thinking skills affect their ability to write argumentative texts using a quantitative approach and a predictive design. The population in this study amounted to 62 students of a private vocational school in Jakarta. Samples were taken of as many as 25 students using the random sampling technique. Both data were obtained by conducting a critical thinking test that adapted the Watson-Glaser theory and an argumentative text writing test. The data analysis used is the Lilliefors test, linearity, and analysis of variance. This study shows that students with higher critical thinking test scores get higher scores in writing argumentative texts and vice versa. Moreover, there is a significant effect of students' critical thinking skills on their argumentative writing skills. Critical thinking ability is one factor that supports students' success in developing written ideas so that the right stimulus is needed to bring up students' critical thinking skills.